Jaccard index with yager class t-norm for ranking fuzzy numbers / Nazirah Ramli, Nurul Haziqah Mohamad, Marina Mohamad and Fairuz Shohaimay - Mohamad, Nurul Haziqah; Mohamad, Marina; Shohaimay, Fairuz (Faculty of Business Management, 2013)
This study proposes a new method for ranking fuzzy numbers based on Jaccard similarity measure index and Yager class t-norm. The procedure of this new ranking method involves six phases which are determining fuzzy maximum and fuzzy minimum, intersection and union of fuzzy numbers, scalar cardinality of fuzzy numbers, fuzzy evidence, fuzzy total evidence and pairwise ranking. The result shows that for certain conditions, the ranking is affected by the values of w and has improved some of the previous results that cannot discriminate the ranking of the fuzzy numbers. Results from this study can be of practical significance to fuzzy decision-making in real situations.